2021
DOI: 10.1111/ajo.13433
|View full text |Cite
|
Sign up to set email alerts
|

Induced abortion in Papua‐New Guinea: Experience and opinions of health professionals

Abstract: Background: Papua-New Guinea (PNG) has one of the highest maternal mortality rates in the world; complications due to unsafe abortion are an important cause.Abortion laws are restrictive, and safe, induced abortions are unavailable to the majority of women, while unsafe abortions are known to be practised throughout the country. The topic of abortion is stigmatised, for women and health professionals. Aim:To conduct a study of PNG health professionals' experience of induced abortion and their views on the prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…PAC involves counseling to respond to the patient’s needs, treatment for incomplete abortion and complications arising from abortion, and the provision of family planning and other reproductive health services [ 13 ]. Reasons for the high proportion of deaths due to unsafe abortion are manifold, as individuals may not be able to access safe, legal abortions, may not be able to access PAC for complications following a spontaneous or induced abortion, or, even with access to medical institutions, may encounter healthcare professionals who decline to provide care [ 14 21 ]. Despite these and other barriers, some evidence has shown that healthcare professionals may be supportive of providing lifesaving PAC, though they are constrained by the health institutions in which they work [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…PAC involves counseling to respond to the patient’s needs, treatment for incomplete abortion and complications arising from abortion, and the provision of family planning and other reproductive health services [ 13 ]. Reasons for the high proportion of deaths due to unsafe abortion are manifold, as individuals may not be able to access safe, legal abortions, may not be able to access PAC for complications following a spontaneous or induced abortion, or, even with access to medical institutions, may encounter healthcare professionals who decline to provide care [ 14 21 ]. Despite these and other barriers, some evidence has shown that healthcare professionals may be supportive of providing lifesaving PAC, though they are constrained by the health institutions in which they work [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Restricting access to abortion serves only to increase the number of unsafe abortions and the associated maternal morbidity and mortality as witnessed by our neighbours in Papua-New Guinea (PNG). 8,9 Another gain for reproductive autonomy has been the introduction of safe access zones in all jurisdictions in Australia allowing pregnant people and staff to attend services free from harassment. Similarly, a Member's Bill is currently being considered in the New Zealand parliament to grant safe areas around abortion services.…”
mentioning
confidence: 99%
“…Abortion legislation in this low and middle income country is contained within criminal law (originally from 1899) and the sequelae of unsafe abortion such as sepsis including puerperal sepsis, are reported as the second leading cause of maternal mortality. 9 Women are known to attempt abortion using unsafe methods such as traditional herbal abortifacients and physical and mechanical means. The use of misoprostol acquired from friends and relations who are health workers, for self-induced abortion is increasing, particularly among educated women.…”
mentioning
confidence: 99%
See 2 more Smart Citations